Effect of Concentration of Soursop Pulp with Ginger and Arabic Gum Concentration on the Quality of Fruit Leather - M. Albi Putra; Rona J. Nainggolan; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The aim of this research was to find the effect of ratio of soursop and ginger pulps with several arabic gum concentration on the quality of soursop and ginger fruit leather. This research was conducted by using completely randomized design with two factors, i.e. :ratio of soursop and ginger pulps (S) : (75% : 25% ; 80% : 20% ; 85% : 15% ; 90% : 10%; 95% : 5%) and arabic gum concentration (K): (0,5%, 1%, 1,5% ). Parameters analyzed were moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid, organoleptic score of colour, taste and texture and organoleptic hedonic values of colour, flavour, taste, and texture. The results showed that the ratio soursop and ginger pulps had highly significant effect on moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid, score of colour, taste and texture, and hedonic values of taste and texture. Arabic gum concentration had highly significant effect on moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid. Interactions of the two factors had highly significant effect on moisture content and crude fiber content, and had no effect on ash content, vitamin C content, total solubility solid, total acid, scores of colour, taste and texture, and hedonic values of colour, flavor, taste and texture. The ratio of soursop and ginger pulps of (95% : 5%) and Arabic gum concentration of (1,5%) produced the best quality of fruit leather and more acceptable. Keywords: Arabic gum, fruit leather, ginger, soursop.